2018
DOI: 10.1121/1.5068254
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sound field isotropy based on directional energy decay curves

Abstract: The analysis of the diffuseness of sound fields is of great interest in room acoustic applications ranging from the analysis of concert venues to reverberation room design and calibration. However, a standardized robust diffuseness estimation method is currently lacking. The fundamental definition of the diffuse sound field is that it is isotropic—requiring the sound field to be composed of infinitely many sound waves from uncorrelated sources with directions of arrival uniformly distributed over a sphere. Due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, only comparative result were presented in his research. Directional energy decay curve was presented in (Berzborn, et al, 2019). The author present a model that sound decay analysis measurement contain clear inconsistencies.…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…However, only comparative result were presented in his research. Directional energy decay curve was presented in (Berzborn, et al, 2019). The author present a model that sound decay analysis measurement contain clear inconsistencies.…”
Section: Review Of the Related Literaturementioning
confidence: 99%
“…While reverberation is often described as diffused in time, recent acoustics measurement research has demonstrated that reverberant sound fields are not necessarily isotropic [22,23,6,24], and may have perceptually salient position-and direction-dependent decay characteristics [25], which should also be considered in 6dof auralization [26]. However, since the perceptual effect of anisotropic reverberation will vary from one room to another and the perceptual threshold of such characteristics has not yet been fully established, more research is required to fully understand this aspect.…”
Section: Introductionmentioning
confidence: 99%